Sunscreen Lotion of Miana Leaves (Coleus atropurpureus Benth) - Rolan Rusli; Rosniah Rosniah; Aditya Fridayanti (Journal of Tropical Pharmacy and Chemistry, 2019)
Sunscreen can protect the skin from the UV radiation. One of the plants that have the potential to be utilized as active ingredients of sunscreen lotion is miana leaves (Coleus atropurpureus Benth). Lotion made in 3 formulas F1, F2 and F3. Lotion tested its stability with a freeze-thaw method, and evaluated organoleptic, homogeneity, pH, viscosity and scatterness and tested sunscreen activity of lotion preparation. The preparation shows good homogeneity, and has oleum rosae odor and a thick consistency with the lotion color is brown (F1), dark brown (F2) and slightly greenish brown (F3). Spreading, viscosity, and pH of the lotion meet the Indonesia Standart requirement. The lotion formula comes in the category of fast tanning (F2) and extra protection (F3) sunscreen.